Rapid thermokarst evolution during the mid-Holocene in Central Yakutia, Russia. (December 2017) - Ulrich, Mathias; Wetterich, Sebastian; Rudaya, Natalia; Frolova, Larisa; Schmidt, Johannes; Siegert, Christine; Fedorov, Alexander N; Zielhofer, Christoph
The reconstruction of Holocene thermokarst landform evolution is important to understand the potential impact of current global climate change on permafrost regions. A multi-proxy approach was applied to analyse the sedimentological and biogeochemical characteristics as well as pollen and lacustrine microfossils of a core profile drilled in a small pingo within a large Central Yakutian thermokarst basin (alas). Age–depth modelling with macrofossil 14 C ages reveals high thermokarst deposit sedimentation rates and a complete thermokarst sequence spanning about 900 years during the mid-Holocene between 6750 and 5870 cal. yr BP. In total, three stages of thermokarst landscape evolution have been identified. Thermokarst processes were initiated at ⩽6750 to 6500 cal. yr BP. Terrestrial conditions changed quickly to lacustrine conditions, and a thermokarst lake rapidly emerged and grew to an estimated size of 120–600 m diameter and 7.5–15 m depth during only 150 years between 6500 and 6350 cal. yr BP. The decline of thermokarst processes and lake decrease may have been affected by local hydrological conditions between 6350 and 5870 cal. yr BP but ceased completely after 5870 cal. yr BP, likely due to climatic changes. Clear evidence for long-lasting and stable lacustrine conditions was not obtained. The study emphasises that short-term warming led to very active permafrost degradation and rapid but locally variable modification of alas and thermokarst evolution.